Geographic Localization of International Technology Diffusion - Keller, Wolfgang (American Economic Review, 2002)
Income convergence across countries turns on whether technological knowledge spillovers are global or local. I estimate the amount of spillovers from R&D expenditures on a geographic basis, using a new data set which encompasses most of the world's innovative activity between 1970 and 1995. I find that technology is to a substantial degree local, not global, as the benefits from spillovers are declining with distance. The distance at which the amount of spillovers is halved is about 1,200 kilometers. I also find that over time, technological knowledge has become considerably more global. Moreover, language skills are important for spillover diffusion.